Guyana climate change action plan in response to its commitments to the UNFCCC : actions for addressing climate change ([s.n.] [S.l.], 2002)
Seeks to address climate change and its adverse impacts on Guyana.
Supplement to Guyana initial national communication in response to its commitments to the UNFCCC